Oriented Polarization Tuning Broadband Absorption from Flexible Hierarchical ZnO Arrays Vertically Supported on Carbon Cloth. Issue 18 (8th April 2019) - Wang, Lei; Li, Xiao; Li, Qingqing; Yu, Xuefeng; Zhao, Yunhao; Zhang, Jie; Wang, Min; Che, Renchao
Abstract: A novel strategy is used to design large‐scale polarized carbon‐based dielectric composites with sufficient interaction to electromagnetic waves. Highly uniform polar zinc oxide arrays are vertically grown on a flexible conductive carbon cloth substrate (CC@ZnO) via an in situ orientation growth process. Anion regulation is found to be a key factor to the morphology of hierarchical ZnO arrays including single‐rod, cluster and tetrapod‐shaped. As a typical dielectric loss hybrid composite, the electromagnetic parameters of the CC@ZnO system and charge density distribution in polarized ZnO rods confirm that the 3D intertwined carbon cloth is used as a conductive network to provide ballistic electron transportation. Moreover, the defect‐rich ZnO arrays are well in contact with the CC substrate, favoring interface polarization, multiscattering, as well as impedance matching. Surprisingly, the efficient absorption bandwidth of the CC@ZnO‐1 composite can reach 10.6 GHz, covering all X and Ku bands. The oriented ZnO possesses oxygen vacancies and exposure to a large amount of intrinsic polar surfaces, encouraging the polarization behavior under microwave frequency. Optimized CC@ZnO materials exhibit fast electron transportation, strong microwave energy dissipation, and superior wide absorption. The results suggest that the CC@ZnO composites have promising potential as flexible, tuning, and broadband microwave absorbers. Abstract : Anion‐regulated polarized ZnO arrays are vertically supported on a carbon cloth network, and these flexible hierarchical carbon cloth/zinc oxide composites show tunable broadband microwave absorption.